2008
DOI: 10.1002/pip.822
|View full text |Cite
|
Sign up to set email alerts
|

19·9%‐efficient ZnO/CdS/CuInGaSe2 solar cell with 81·2% fill factor

Abstract: We report a new record total-area efficiency of 19Á9% for CuInGaSe 2 -based thin-film solar cells. Improved performance is due to higher fill factor. The device was made by three-stage co-evaporation with a modified surface termination. Growth conditions, device analysis, and basic film characterization are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
1,049
2
8

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,003 publications
(1,103 citation statements)
references
References 13 publications
8
1,049
2
8
Order By: Relevance
“…A power meter that is sensitive to the ultraviolet light was put in a position of 1.5 cm above the solar cell, and a convex lens was put above the power meter. We observed that the power of solar irradiation I is related to the distance between the lens and the power meter y within the focal length in the form I = I0 + k (y) 2 , where I0 and k are constants. This relation allowed us to find the position of lens for a desired power density on the solar cell.…”
Section: J -V Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A power meter that is sensitive to the ultraviolet light was put in a position of 1.5 cm above the solar cell, and a convex lens was put above the power meter. We observed that the power of solar irradiation I is related to the distance between the lens and the power meter y within the focal length in the form I = I0 + k (y) 2 , where I0 and k are constants. This relation allowed us to find the position of lens for a desired power density on the solar cell.…”
Section: J -V Measurementsmentioning
confidence: 99%
“…Recently, the Cu(In,Ga)Se2 (CIGS) thin-film solar cell has been the subject of intensive research and development in the photovoltaic industry [1][2][3][4][5][6]. CIGS has a great potential for solar cells with high power-conversion efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Now the most developed thin film photovoltaic technologies are based on CdTe and CuInSe 2 absorber layers. Recently a maximum efficiency of 19.9% has been achieved at National Renewable Energy Laboratory, United States of America, using Cu(In,Ga)Se 2 based absorber layers [1]. But these materials, due to the difficulty in maintaining stoichiometry, especially in large area films, alleged environmental hazards and high cost of indium are not beneficial in the longer run [2].…”
Section: Introductionmentioning
confidence: 99%
“…MOCVD is a reliable technique for the fabrication of high-efficiency solar cells [3], and solar cells with efficiencies between 10% and 19% can be obtained. More generally, efficiencies of the order of 20%, measured under the AM 1.5 global spectrum for 1000 W/m2 irradiance, have been achieved in the lab for epitaxially grown CuIn x Ga (1−x) Se 2 -based solar cells [4,5]. There are other methods to grow chalcopyrite thin films.…”
Section: Introductionmentioning
confidence: 99%